Deformação plástica severa em temperaturas ambiente e criogênica, de Ti comercialmente puro - Mendes Filho, Anibal de Andrade (Universidade Federal de São Carlos, 2015)
One of the most probable fields of applications of Severe Plastic Deformation (SPD) processes is that of biological implants, and the most investigated metallic material in this context is titanium and its alloys. The motivation for the present work follows a general tendency which aims to substitute the Ti-6Al-4V alloy for commercially pure Ti; a prerequisite for such replacement being the mechanical strength enhancement of the latter. Lower cost and the absence of the harmful Al and V justify the substitution. For the purpose of strength enhancement a number of SPD processes are available, but very recent investigations showed that the combination of Equal-channel angular pressing (ECAP) with rolling or extrusion gives excellent results. In this work SPD was applied to commercial Ti Grade 2 employing (i) four ECAP passes; (ii) same followed by rolling, at room temperature and (iii) same followed by rolling at 100oC. The focus of the investigation is centred on process (iii), its influence on mechanical properties, work hardening capacity, sensitivity to strain rate, grain size and microstructure. Highest mechanical strength among all other process conditions was produced by only two ECAP passes plus rolling at 100oC. This was achieved by the establishment of a very small grain size and a high density of dislocations. The sub-zero mode of deformation also affected positively the high cycle fatigue behaviour, the Charpy fracture energy and the thermal stability; that was determined by microhardness measurements and calculation of the activation energy for recrystallization employing DSC. Additionally were investigated a series of properties here called technological properties of utmost importance for the final product: Results show that sub-zero SPD is harmful to machinability, benefits corrosion and produces screws for bone implants whose torque limit is above this product specifications but its torque fracture angle is smaller than for the Ti-6Al-4V alloy.
Microstructural evolution and properties of pure titanium grade 2 subjected to severe plastic deformation
Keywords: Titânio; Deformação plástica severa; Fadiga; Implantes ortopédicos; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA